Suggested policies in regard to Suburban expansion into the Urban fringe (the Constantia Village), book 1 - Callaghan, Bernard Mark (Urban Management, 2020)
This study is based on identifying and analysing the problems which arise from suburban expansion into the urban fringe; and on suggesting certain policy measures which could serve as a basis for directing development in such a way as to avoid these problems. The urban fringe is recognized as the contact zone between the city and the countryside. As such, it experiences the major development forces which arise from the growth of the metropolitan population. It is characterised by change and instability; which are reflected in unrealistic land values, speculative land holding, and unproductive use of much of the land. As suburban development encroaches into this zone, so the forces which precede it reach further out into the countryside. Many fringe areas comprise prime farmland and, in some instances, the environmental characteristics of the l and are scenically attractive and offer great opportunities for meeting the outdoor recreational needs of the metropolitan population. The threat to these attributes. constitutes the major problem associated with suburban expansion.